Pelestarian Wayang “Krucil” dan Kekuatan Politik - Dian Suluh Kusuma Dewi; Yusuf Adam Hilman (Institut Teknologi Sepuluh Nopember, 2018)
Purpose of the article is to analyze the preservation of puppets “Krucil” andthe politic of powers happens in Tempuran village, Sawoo Sub-District,Ponorogo Regency. The method of the article is qualitative descriptive researchand it uses in-depth interview for collecting the data. The finding of the studyshow that; the preservation of the puppets “Krucil” held by the government ofTempuran village annually is by having performance in “BersihDesa”(annually societies’ activity for thanking to God after they get crop)activity. The performance of puppets “Krucil” in “Bersih Desa” activity toentertain the society have been doing since the village founded. The series ofevents of preservation of puppets “Krucil” are “Ruwatan” ritual conducted byevery (head of hamlet), “Brokohan” and recitation of holy Qur’an. While,politic of powers was conducted by including “Bersih Desa” activity andperformance of puppet “Krucil” to the village regulations. It was conducted bythe head of village in Tempuran District based on the strong of society’s myth.The societies believe that there will be crop failure and prolonged disaster if“Bersih Desa” activity don’t performance puppets “Krucil”.